Enhancing women’s assets to manage risk under climate change: Potential for group-based approaches - Ringler, Claudia; Quisumbing, Agnes R.; Bryan, Elizabeth; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2014)
The project “Enhancing Women’s Assets to Manage Risk under Climate Change: Potential for Group-Based Approaches” aims to help poor women farmers and pastoralists in Africa south of the Sahara and South Asia—especially those in Ethiopia, Kenya, Mali, and Bangladesh—manage risks under climate change. The notes in this collection explore how to protect or strengthen women’s control over critical assets, including natural resources and social capital. These notes also examine the potential for innovative and group-based approaches to increase women’s assets and strengthen their risk-management capabilities in the context of climate change.